Increased level of red cell distribution width is associated with poor coronary collateral circulation in patients with stable coronary artery disease - İrfan Şahin; Ahmet Karabulut; Adnan Kaya; Barış Güngör; Ilhan Ilker Avcı; Ertugrul Okuyan; Mehmet Mustafa Can; Serhat Sığırcı; Burak Ayça; Mustafa Hakan Dinckal (KARE Publishing, 2015)
Objectives: Previous studies have shown the association between various hematological parameters and cardiovascular diseases, and their prognostic value. In this study, we compared red cell distribution width (RDW), neutrophil lymphocyte ratio (NLR) and mean platelet volume (MPV) measurements among patients with poor coronary collateral circulation (CCC) and well-developed CCC. Study design: 326 patients with stable coronary artery disease (CAD) were evaluated retrospectively. CCC was graded by using the Rentrop classification. The poor CCC group included patients with Rentrop 0-1 CCC, and the good CCC group included Rentrop 2-3 CCC. Results: There were 171 subjects (84% male; mean age 56.6+-10.4 years) in the poor CCC group, and 155 subjects (89% male; mean age 57.6+-9.7 years) in the good CCC group. The total number of vessels with >95% stenosis (1.1+-0.5 vs. 1.0+-0.4; p=0.64) and Gensini scores (84.4+-38.8 vs. 83.3+-37.4; p=0.83) was not higher in the poor CCC group compared to the good CCC group. RDW was significantly higher in the poor CCC group compared to the good CCC group (14.19+-1.36% vs. 13.89+-1.19%; p=0.04). In multivariate logistic regression analysis, elevated levels of RDW and LDL were found to be independent predictors of poor CCC (OR 1.73, 95% CI: 1.30-2.29, p=0.01 and OR 1.01 95% CI 1.002-1.02; p=0.02, respectively). Conclusion: In the present study, poor CCC was found to be independently correlated with RDW, but not with any other hematological parameters in patients with stable CAD.